2018
DOI: 10.1089/jayao.2018.0022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fitbit and iPad Wearable Technology in Health-Related Quality of Life in Adolescent and Young Adult Cancer Patients

Abstract: Distributing wearable technology at the time of diagnosis may provide an avenue for improving HRQOL in adolescents and young adults with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 17 publications
1
23
0
1
Order By: Relevance
“…Our results are comparable to previous studies that have used similar methods of EB data collection, including the use of wearable fitness trackers in young adult cancer patients, and found them to be feasible and acceptable [50]. However, the previous study did not include a nutrition component.…”
Section: Discussionsupporting
confidence: 82%
“…Our results are comparable to previous studies that have used similar methods of EB data collection, including the use of wearable fitness trackers in young adult cancer patients, and found them to be feasible and acceptable [50]. However, the previous study did not include a nutrition component.…”
Section: Discussionsupporting
confidence: 82%
“…Studies on the clinical impact of wearables on patient health outcomes offer varied results. Although some conditions such as physical activity and sleep did not show significant or conclusive change from wearable technology use and require further evaluation, other studies have reported improved subjective outcomes on patient health [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Use was associated with improvements in self-reported physical well-being, spirituality, palliative quality of life, and general quality of life Described the program as an opportunity to improve health and provide self-care Yurkiewicz et al (2018) Prospective cohort study of the association between wearable activity tracking technology (Fitbit) and educational material (synced iPad) and quality of life over the course of 6 months Statistically significant improvements in physical functioning, role function/physical reports, role function/emotional reports, energy and fatigue, emotional well-being, social functioning, pain, and general health 85% Enjoyed using the technology, 79% felt it helped them be more active, 58% used a meditation app, 27% played a cancer-related video game, and 27% participated in online social communities Clinical interactions…”
Section: Creative Expressionmentioning
confidence: 99%
“…Participants in this study were encouraged to make an online profile (that could be anonymous) to interact in a virtual cancer-specific peer community. The majority (58%) of participants used the mediation app, but only 27% played Remission 2™ or participated in the online social community (Yurkiewicz et al, 2018). When compared with baseline scores, use of the technology was associated with improvements in self-reported physical functioning (p < .00), role function (p < .00), energy/ fatigue (p < .00), emotional well-being (p = .01), social functioning (p < .00) pain (p < .00), and overall general health (p = .01); but was not reported as being readily accepted by AYAs (Yurkiewicz et al, 2018).…”
Section: Engaging Technologymentioning
confidence: 99%
See 1 more Smart Citation